English English - Ningias, Rista Ananda; Indriani, Lilia (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
This article investigates the students’ responses toward corrective feedback effectiveness for EFL students' speaking skills that constitute negative feedback. It is the form of linguistic error response toward the learner's error utterance (Zhang & Chatupote, 2014). The most popular corrective feedbacks in teaching speaking are explicit correction, elicitation, and repetition (Muhsin, 2016). This article aimed to analyze the students’ responses toward the effectiveness of corrective feedback in increasing EFL students speaking performance. The researcher researched 35 EFL students of the English Department Student at Tidar University. This study applied a quantitative approach in analyzing the data by sending the questionnaire consist of six categories. The researcher used the questionnaire to collect data about the participants' responses towards using corrective feedback in students' speaking performance. The result shows that implementing corrective feedback is effective for increasing EFL students' speaking performance. Keywords: Corrective Feedback, Effectiveness, Speaking, EFL Students